2001
DOI: 10.1037/0033-2909.127.1.87
|View full text |Cite
|
Sign up to set email alerts
|

Coping with stress during childhood and adolescence: Problems, progress, and potential in theory and research.

Abstract: Progress and issues in the study of coping with stress during childhood and adolescence are reviewed. Definitions of coping are considered, and the relationship between coping and other aspects of responses to stress (e.g., temperament and stress reactivity) is described. Questionnaire, interview, and observation measures of child and adolescent coping are evaluated with regard to reliability and validity. Studies of the association of coping with symptoms of psychopathology and social and academic competence … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

126
2,588
11
145

Year Published

2003
2003
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 2,477 publications
(2,870 citation statements)
references
References 175 publications
126
2,588
11
145
Order By: Relevance
“…Interestingly, this pathway did not hold for the adults in the study; rather, coping strategies moderated the association between stress and psychopathology. Although these findings and other studies support the assertion that coping strategies during childhood and adolescence may be context-dependent and susceptible to influences directly from the stressor (Compas et al 2001;Wadsworth et al 2005), none of these studies have focused exclusively on social stressors that may be most salient to adolescents (i.e., peer stress and pubertal timing).Although research supports the notion that stress may impact the availability of coping resources and an adolescent's type of response, in turn increasing the risk for psychopathology (i.e., mediation as described above), children and adolescents do have prior tendencies toward certain stress responses (e.g. physiological arousal, anger, denial).…”
contrasting
confidence: 42%
See 1 more Smart Citation
“…Interestingly, this pathway did not hold for the adults in the study; rather, coping strategies moderated the association between stress and psychopathology. Although these findings and other studies support the assertion that coping strategies during childhood and adolescence may be context-dependent and susceptible to influences directly from the stressor (Compas et al 2001;Wadsworth et al 2005), none of these studies have focused exclusively on social stressors that may be most salient to adolescents (i.e., peer stress and pubertal timing).Although research supports the notion that stress may impact the availability of coping resources and an adolescent's type of response, in turn increasing the risk for psychopathology (i.e., mediation as described above), children and adolescents do have prior tendencies toward certain stress responses (e.g. physiological arousal, anger, denial).…”
contrasting
confidence: 42%
“…Based on prior vulnerabilities and prior experiences, adolescents often respond to such negative peer events with a range of reactions-anger, sadness, aggression, emotional suppression, etc. In turn, how an adolescent adapts to these experiences is often associated with the expression of emotional and behavioral problems (Compas et al 2001). …”
mentioning
confidence: 99%
“…Cognitive coping can be defined as the cognitive way of managing the intake of emotionally arousing stimuli [6,9,30]. Cognitive coping is distinguished from other partially overlapping constructs, such as emotion regulation and mood regulation, by its predominant focus on decreasing negative affect in response to stressful situations [14,28].…”
Section: Introductionmentioning
confidence: 99%
“…Cognitive coping is distinguished from other partially overlapping constructs, such as emotion regulation and mood regulation, by its predominant focus on decreasing negative affect in response to stressful situations [14,28]. Cognitive coping is considered to act as a mediator and moderator of the association between stress and psychological well being [6,7]. Cognitive coping might be particularly important to examine in relation to childhood anxiety disorders, as anxiety-disordered children experience significantly more stressful situations (i.e., negative life events) than their non-anxious counterparts and perceive these situations as more threatening [1,13,19].…”
Section: Introductionmentioning
confidence: 99%
“…Others studies revealed clear differential effects of behavioral and cognitive coping strategies (e.g., [71,72]). This suggests that the distinction between cognitive and behavioral coping requires more examination and future studies in this area could benefit from exploration of other potential classification frameworks (e.g., stress and temptation coping paradigm [73], engagement or problem-focused coping, emotionfocused or disengagement coping) [74].…”
Section: Original Researchmentioning
confidence: 99%